Aplikasi Penentuan Kelayakan Penerima Kredit pada Kopdit Swasti Sari Menggunakan Metode Profile Matching - Maximilianus Benge; Frengky Tedy; Yovinia Carmeneja Hoar Siki (CESS (Journal of Computer Engineering, System and Science), 2021)
KSP Kopdit Swasti Sari is one of the credit cooperatives in East Nusa Tenggara.  One of the activities carried out by the KSP Kopdit Swasti Sari to improve the welfare of its members is to provide credit to provide credit to its members. However, the credit service procedure at the KSP Kopdit Swasti Sari is still not effective and efficient. Therefore, the KSP Kopdit Swasti Sari requires a computerized method in order to streamline its performance. The profile matching method in a decision support system is one method that can be applied to provide solutions to existing problems. This system is able to determine which members are eligible for credit. Besides, it also makes it easier for members in administrative processes such as registration and transactions.